The effects on human health of non-metallic, semimetals and heavy metals compounds generated by mining activities along the Serbian-Romanian border - Bianca-Vanesa Boros; Diana-Larisa Roman; Vasile Ostafe; Radmila Markovic; Vojka Gardic; Zoran Stevanovic; Adriana Isvoran (Romanian Journal of Ecology & Environmental Chemistry, 2021)
This study makes an overview of the chemical pollutants, such as Be and its compounds, S and its compounds, P and its compounds, chlorine and chlorides, Na2O, K2O, Ti2O, CaO, MgO, CuO, SiO2, Al2O3, Fe2O3, Cr2O3, As2O3, that were registered in the mining operations areas in the cross-border region of Romania and Serbia. In addition, their possible effects on human health were discussed. Among the oxides, SiO2, Al2O3, Fe2O3 are the most abundant. From all these pollutants, the most health effects were registered for the compounds of P, S and Ca and the lowest number of health effects was recorded for chlorine. Among the human health effects that have been observed for these compounds, the most common are related to skin, eye and respiratory irritations in the case of acute exposure, but chronic exposure may lead to diseases affecting all the human organs. This information is important for population living in this area, due to air, water and soil pollution, but especially for professional exposure as workers in the mining operations are exposed to higher concentrations of pollutants and for long time.